2019
DOI: 10.1177/0361198119838854
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Highway Capacity Manual Urban Street Travel Time Reliability Methodology using Empirical Data

Abstract: The 6th edition of the Highway Capacity Manual (HCM-6) includes the concept of travel time reliability (TTR), which attempts to determine the distribution of average trip travel times over an extended period. TTR is an inherent part of travelers’ route choice decisions and is used by traffic managers to better quantify operations rather than simply using average travel times. The focus of this paper is on the HCM-6 urban street TTR methodology contained in Chapter 17. The approach uses historical data (e.g., w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…In other words, the HCM-6 TTR metrics indicated that the testbed was more reliable than field measurements would indicate. Similar results were also shown on a 0.8-km (0.5-mi) testbed in Lincoln, Nebraska (Tufuor and Rilett 2019).…”
Section: Introductionsupporting
confidence: 79%
“…In other words, the HCM-6 TTR metrics indicated that the testbed was more reliable than field measurements would indicate. Similar results were also shown on a 0.8-km (0.5-mi) testbed in Lincoln, Nebraska (Tufuor and Rilett 2019).…”
Section: Introductionsupporting
confidence: 79%
“…BT-based traffic data has been frequently used in traffic analysis due to the higher sampling rate and low cost [12]. While some studies focused on the reliability of travel times for freeways or urban arterials [3][4][5][6][7][8][9][10], some other studies focused on the estimation of origindestination matrix [2,[13][14][15], freeway performance evaluation [10,[16][17], traffic safety analysis [18], delay estimation for signalized intersections [19][20][21]. Since the focus of this study is to examine the reliability of TT data, it is useful to present the TT related studies in this section.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for literature on the Bluetooth-based studies, the accuracy or variability of the travel times has been investigated particularly for freeways or multilane highways [3][4][5][6][7], whereas there were limited studies regarding the travel time reliability for urban arterials controlled with traffic signals [8][9][10] which is the main focus of this study. For this purpose, BT-based travel time data was collected for two days (October 8-9, 2019) during morning peak hours (07:30-09:30) from five consecutive intersections located on major urban arterials in Mersin, Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Bluetooth detectors have been installed in the traffic cabinets for collecting empirical point-to-point Bluetooth travel time (BT) data. A comprehensive analysis of the BT data collection system, its filtering algorithm, and a validation process are provided elsewhere (11). The BT sampling rate was from 4% to 6%, which falls within the detection range of similar travel time studies (12)(13)(14).…”
Section: Testbed and Field Data Descriptionmentioning
confidence: 99%